Analysis of the Effect of Promotion and Dissatisfaction on Digital Wallet Brand Switching through the Need to Find Variations in Case Study on Ovo - Santika, Febi; Kurniasari, Florentina (International Journal of Business and Applied Economics, 2025)
The growth of e-wallet users in Indonesia shows a very positive trend, the number of e-wallet users increases significantly every year. Some of the reasons Indonesians prefer to use digital payments or e-wallets are because they feel more comfortable, fast transactions, no need to carry a lot of cash and cards, easy to use, easier to track expenses, safer and more hygienic, until there are various promotions that provide benefits for users. However, amidst the growth in the number of e-wallet users in Indonesia, OVO as one of the leading digital wallets in Indonesia has experienced a downward trend until it is difficult to compete with its competitors such as Gopay and Shopeepay. This study aims to determine how the influence of promotion and dissatisfaction on brand switching through the need to seek variations of OVO e-wallet users in Jakarta. The sample used in this study amounted to 127 respondents using non-probability sampling techniques. The results showed that promotion affects brand switching, dissatisfaction affects brand switching, the need to seek variety influences brand switching, and the need to seek variety can be a mediating variable in this study.